Coral-associated decapods (Crustacea) from the Mexican Tropical Pacific coast - Hernández, Luis; Ortiz, Georgina Ramírez; Reyes-Bonilla, Héctor (Zootaxa, 2013)
Our study provides a checklist of 36 crustacean decapods from the Mexican tropical Pacific coastline. Most of the species were previously recorded from coral communities in the Gulf of California. Data were obtained by visual censuses of coral communities and some specimens were collected by extractions of coral branches (approximately eight liters of coral volume). We found new geographic records for three species from the Eastern Pacific and seven species that have extended ranges into Mexican waters. Only one species is documented with a northerly range from Central America to Mexican waters.